Multimorbidity increases risk of cardiovascular outcomes in permanent atrial fibrillation: Data from the RACE II study - Colinda van Deutekom; Marieke J.H. Velt; Isabelle C. van Gelder; Michiel Rienstra; Bart A. Mulder (International Journal of Cardiology: Heart & Vasculature)
Introduction: Multimorbidity is common in patients with atrial fibrillation (AF), but data on its prevalence and impact in permanent AF is limited. This study aimed to investigate the prevalence of multimorbidity and its association with cardiovascular outcomes in recent-onset permanent AF. Methods: The RACE II study was a randomized controlled trial comparing strict and lenient rate-control in 614 patients with recent-onset permanent AF. Presence of nine comorbidities was assessed and the population divided into three groups based on the number of comorbidities (0–1, 2–3, ≥4). Cox regression analyses were conducted to assess the association between the number of comorbidities and the primary composite outcome (cardiovascular mortality, hospitalization for heart failure, stroke and/or systemic embolism, major bleeding, arrhythmic events). Kaplan-Meier estimates for the cumulative risk of the first event were calculated and plotted. Results: Mean age was 68 ± 8 years and 211 (34 %) were women. In this population, 213 (35 %) patients had 0–1 comorbidity, 313 (51 %) 2–3, and 88 (14 %) ≥ 4. During 3 years follow-up, 81 patients (13 %) reached the primary composite outcome. Patients with more comorbidities more frequently reached the primary composite outcome (P < 0.001), as well as cardiovascular mortality (P = 0.049), heart failure hospitalizations (P = 0.003), and stroke/systemic embolism (P = 0.024). The presence of ≥ 4 comorbidities was associated with a higher risk of the primary composite outcome compared to the presence of 0–1 comorbidity (HR 2.27, 95 % CI (1.21–4.23), P = 0.010). Conclusion: Multimorbidity was present in two-thirds of recent-onset permanent AF patients, with a higher number of comorbidities associated with greater risk of cardiovascular outcomes.